MORPHOLOGICAL CHANGES IN CULTURED GRANULOSA CELLS FROM DIFFERENT SIZED FOLLICLES OF GOAT OVARY - SANGHA, G K; KAUR, H K; KHERA, K S (The Indian Journal of Animal Reproduction, 2023)
The granu/osa cells (GCs) from small (5) mm follicles of immature and maturegoat ovary were aspirated and cultured in complete culture medium (McCoy's SA medium) for studying themorphology and size related changes. GCs formed clus1ers of flattened cells with typical epitheloid morphology.The number of clusters and the GCs per cluster increased with growth of the follicle as well as with the growth ofovary. A progressive increase in diameter of granulosa cells was also observed with maturation of ovary. The celldiameter almost doubled between the small and large follicles of both immature and mature ovary.
Keywords: Granulosa cell; Morphology; Size; Culture; Follicles; Goat